Combined 3D building surveying techniques – terrestrial laser scanning (TLS) and total station surveying for BIM data management purposes - Mill, Tarvo; Alt, Aivars; Liias, Roode (Journal of Civil Engineering and Management, 2014)
Building information modelling (BIM) represents the process of development and use of a computer generated model to simulate the planning, design, construction and operation of a building. The utilisation of building information models has increased in recent years due to their economic benefits in design and construction phases and in building management. BIM has been widely applied in the design and construction of new buildings but rarely in the management of existing ones. The point of creating a BIM model for an existing building is to produce accurate information related to the building, including its physical and functional characteristics, geometry and inner spatial relationships. The case study provides a critical appraisal of the process of both collecting accurate survey data using a terrestrial laser scanner combined with a total station and creating a BIM model as the basis of a digital management model. The case study shows that it is possible to detect and define facade damage by integration of the laser scanning point cloud and the creation of the BIM model. The paper will also give an overview of terrestrial laser scanning (TLS), total station surveying, geodetic survey networks and data processing to create a BIM model.First published online: 24 Oct 2013